Estimasi Efisiensi Bank-Bank Umum di Sumatera Barat Melalui Metode Stochastic Frontier Approach (SFA) - Ramadhan, Gaffari (UI Scholars Hub, 2009)
This study estimates the banking efficiency in the Province of West Sumatera for the years of 2007-2008. Using 19 samples of commercial banks, the estimation applies the Stochastic Frontier Approach (SFA) model in order to analyze the cost efficiency of commercial banks. This study finds that the bank's cost function is significantly affected by price of labors, price of funds, and loans. The results of the banking efficiency estimation show that in annually almost banks have more than 80 percent of the efficiency level. In the average estimation, it also shows the same result. By dividing banks into groups, the estimation shows that the government bank is more efficient than the national private bank.